A rare case of ectopic papillary thyroid carcinoma transformed into squamous cell carcinoma. Issue 4 (16th February 2018) - Yasuoka, Hironao; Nakamura, Yasushi; Yoshida, Ken‐ichi; Shimo, Toshiro; Tori, Masayuki; Matsui, Yuuki; Sakamaki, Yasushi; Tsujimoto, Masahiko
Abstract : A rare case of a metastatic ectopic papillary thyroid carcinoma (PTC) of the lung that transformed into a squamous cell carcinoma (SCC) that resembles pulmonary SCC is reported. A subcutaneous ectopic PTC in the left anterior neck area, together with a normal thyroid gland, were excised. The ectopic PTC showed thyroglobulin, TTF‐1 and PAX‐8 immunoreactivity and a BRAF V600E mutation. During the post‐operative follow‐up period, a rapidly growing 2 cm nodular lesion in the lower left lobe of the lung was detected. The lung tumor consisted of solid sheets and nests of squamous cells but without the nuclear features of PTC. Neither papillary nor follicular structures of cancer cells were identified. Carcinoma cells were positive for TTF‐1, PAX‐8, p40, CK14, and p63, while showing a high Ki‐67 labeling index and a BRAF V600E mutation. These results support our interpretation of a PTC that originated from ectopic thyroid tissue in the left anterior neck and that developed a lung metastasis showing squamous cell differentiation.